2021
DOI: 10.1155/2021/4576071
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effects and Mechanism of Buyang Huanwu Decoction on Pulmonary Vascular Remodeling: Network and Experimental Analyses

Abstract: Pulmonary hypertension (PH) is a severe and progressive cardiovascular disease. Its pathological mechanism is complex, and the common pathological feature is pulmonary vascular remodeling. The efficacy of existing therapeutic agents is limited. Traditional Chinese medicine (TCM) has its unique advantages in the prevention and treatment of complex diseases. In this study, the approaches of network pharmacology combined with biological verification are employed to explore the role of Buyang huanwu decoction (BYH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Both TCM and Western medicine involve direct intervention for fibrosis to inhibit fibroblast increase and ECM generation by regulating various fibrosis pathways in the vascular niche. Many studies have shown that in rat models of pulmonary fibrosis, the TCM compound BYHW can reduce the levels of connective tissue growth factor (CTGF) and phosphorylated (p)-AKT, which reduced pulmonary fibrosis in rats, and also regulated the PI3K/AKT/ endothelial nitric oxide synthase (eNOS) pathway to improve pulmonary vascular remodeling [ 102 , 103 ]. In a mouse model of myocardial infarction, BYHW could promote angiogenesis in the infarct border zone, reduce the extent of myocardial infarction, and reduce myocardial fibrosis and inflammation by upregulating the caveolin-1 (Cav1)/VEGF signaling pathway [104] .…”
Section: Treatment Strategies For Organ Fibrosis Using Western and Tr...mentioning
confidence: 99%
“…Both TCM and Western medicine involve direct intervention for fibrosis to inhibit fibroblast increase and ECM generation by regulating various fibrosis pathways in the vascular niche. Many studies have shown that in rat models of pulmonary fibrosis, the TCM compound BYHW can reduce the levels of connective tissue growth factor (CTGF) and phosphorylated (p)-AKT, which reduced pulmonary fibrosis in rats, and also regulated the PI3K/AKT/ endothelial nitric oxide synthase (eNOS) pathway to improve pulmonary vascular remodeling [ 102 , 103 ]. In a mouse model of myocardial infarction, BYHW could promote angiogenesis in the infarct border zone, reduce the extent of myocardial infarction, and reduce myocardial fibrosis and inflammation by upregulating the caveolin-1 (Cav1)/VEGF signaling pathway [104] .…”
Section: Treatment Strategies For Organ Fibrosis Using Western and Tr...mentioning
confidence: 99%
“…Based on this, we propose that the vascular niche is the basic structure of organ ligaments including the kidney and is a good entry point for modern research in ligamentology. Common mechanisms involved in fibrosis include the TGF/Smads pathway [3], some inflammatory signaling pathways such as Wnt/β-catenin, MAPK, NF-κB, PI3K/Akt, and JAK-STAT pathways [4][5][6][7][8], the CXCL12-CXCR4/CXCR7 pathway [9], the endothelial-to-mesenchymal transformation(EMT), and the epithelial mesenchymal transition(EMT) [10,11], as well as the regulation of some inflammatory mediators and cytokines such as hypoxia-inducible factor-1 (HIF-1),peroxisome proliferatoractivated receptors (PPAR-γ), IL-10,IL-13, IL-21, TGF-β1, chemokines (MCP-1, MIP-1beta), angiogenic factors (VEGF), growth factors (PDGF), acute phase proteins (SAP), caspases, and components of the renin-angiotensin-aldosterone system (ANG II) [12][13][14][15]. The cells involved in these mechanisms include parenchymal cells of organs, vascular endothelial cells, pericytes, epithelial cells, myofibroblasts, and various immune cells [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of great significance to further clarify the anti-hepatic fibrosis mechanism of Mongolian medicine scabiosa for the prevention of hepatic fibrosis. Network pharmacol ogy integrates system biology, traditional pharmacology, network analysis, and computer analysis techniques to clarify the mechanism of action of drugs at multiple l evels, which is characterized by integrity, systematization, and novelty [12,13] . At present, most of the anti-liver fibrosis methods highlight the effect on a cell or a signa ling molecule, without considering that hepatic fibrosis is a complex process [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Network pharmacol ogy integrates system biology, traditional pharmacology, network analysis, and computer analysis techniques to clarify the mechanism of action of drugs at multiple l evels, which is characterized by integrity, systematization, and novelty [12,13] . At present, most of the anti-liver fibrosis methods highlight the effect on a cell or a signa ling molecule, without considering that hepatic fibrosis is a complex process [12] . From the current research, it is limited to use traditional biological experimental met hods to explore the mechanism of Mongolian medicine.…”
Section: Introductionmentioning
confidence: 99%